Comparison of In Vitro and In Planta Heavy Metal Tolerance and Accumulation Potential of Different Armeria maritima Accessions from a Dry Coastal Meadow - Līva Purmale; Astra Jēkabsone; Una Andersone-Ozola; Andis Karlsons; Anita Osvalde; Gederts Ievinsh (Plants, 2022)
The aim of the present study was to compare the tolerance to several heavy metals and their accumulation potential of Armeria maritima subsp. elongata accessions from relatively dry sandy soil habitats in the Baltic Sea region using both in vitro cultivated shoot explants and long-term soil-cultivated plants at the flowering stage as model systems. The hypothesis that was tested was that all accessions will show a relatively high heavy metal tolerance and a reasonable metal accumulation potential, but possibly to varying degrees. Under the conditions of the tissue culture, the explants accumulated extremely high concentration of Cd and Cu, leading to growth inhibition and eventual necrosis, but the accumulation of Pb in their tissues was limited. When grown in soil, the plants from different accessions showed a very high heavy metal tolerance, as the total biomass was not negatively affected by any of the treatments. The accumulation potential for heavy metals in soil-grown plants was high, with several significant accession- and metal-related differences. In general, the heavy metal accumulation potential in roots and older leaves was similar, except for Mn, which accumulated more in older leaves. The absolute higher values of the heavy metal concentrations reached in the leaves of soil-grown A. maritima plants (500 mg Cd kg−1, 600 mg Cu kg−1, 12,000 mg Mn kg−1, 1500 mg Pb kg−1, and 15,000 mg Zn kg−1) exceeded the respective threshold values for hyperaccumulation. In conclusion, A. maritima can be characterized by a species-wide heavy metal tolerance and accumulation potential, but with a relatively high intraspecies diversity.